From Intellectual Capital to Value Creation: Innovation Orientation and Financial Capital Innovation as Strategic Mediators - Arif Widodo (CV. Vocezmi Learnov, 2026)
This study aims to examine how intellectual capital contributes to firm value creation by investigating the mediating roles of innovation orientation and financial capital innovation in manufacturing firms. It seeks to move beyond a linear view of intellectual capital by explicating the mechanisms through which knowledge-based resources are transformed into economic value. The study adopts a quantitative explanatory design using secondary data from manufacturing firms operating in Central Java. The proposed conceptual model is tested using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among intellectual capital, innovation orientation, financial capital innovation, and value creation. This research advances the intellectual capital literature by offering a process-oriented explanation of value creation. It extends resource-based and dynamic capabilities perspectives by positioning financial capital innovation as a critical yet underexplored mediating mechanism alongside innovation orientation in translating intellectual capital into firm value. The findings suggest that managers should not only invest in intellectual capital but also actively foster innovation-oriented strategies and innovative financial practices to realize sustainable value creation. For policymakers, the results highlight the importance of supporting innovation ecosystems and financial flexibility, particularly in manufacturing sectors operating under resource constraints. This study is limited by its reliance on secondary data and a cross-sectional design, which may not fully capture the dynamic evolution of intellectual capital and innovation over time. Future research is encouraged to employ longitudinal or mixed-method approaches and to test the proposed model across different industries and institutional contexts.